An experimental assessment of surface micro irregularities (porosity and texture) effects on tribological behaviour under lubricated conditions. - Boidi, Guido (2019)
Energy saving, improving system efficiency and using alternative energy sources are common strategies adopted nowadays for reducing human detrimental impact on environment. In particular, tribologists strive to reduce friction in rubbing parts using coatings, advanced lubricants or modifying surface topography. In this context surface texture has been significantly studied in recent years, although this procedure usually implies extra manufacturing operations and costs. On the other hand, sintered materials contain themselves surface cavities that could potentially act as surface texture and, consequently, lead to friction reduction. This research aims to extend the current knowledge on the tribological influence of micro surface irregularities (pores and laser texture) under lubricated experimental tests and explore the use of these features for tribological applications. Samples were manufactured using both sintering and texturing processes to obtain different surface characteristics. Three different porosity conditions were produced for sintered steels, whereas grooves and dimples configurations were designed for textured steel samples. After that, experimental tests were performed under varying sliding-rolling conditions (from prevalent rolling to prevalent sliding) especially using non-conformal contact. Speed was also varied during frictional tests to cover a wide range of operational conditions and verify the effects of surface features under different lubrication regimes. Friction tests were carried out with two tribometers using configurations of pin-on-disk, roller-on-disk and ball-on-disk. Film thickness was measured by an ultra-thin optical interferometry rig using a methodology properly designed for rough samples. Samples with smooth surfaces were utilized as a reference bench to be compared to material with surface modification (texture or porosity). Main results showed that the decrease of porosity led to friction reduction in the sintered steel. Material with reduced porosity performed even better than reference smooth samples. In addition, the dimple configuration promoted friction reduction, whereas grooves generally performed similarly or worse than reference material. Even if textured dimples and small porosity on sintered material were produced by different techniques, they presented similar geometrical characteristics and consequently they both reduced friction compared to reference samples. As part of the outcome, main results were mapped to better understand the effect of each surface feature on tribological performance. Furthermore, a preliminary phenomenological model was proposed to predict frictional response of surface with micro cavities (pores or texture) from reference steel results. Main findings suggest that the effect of tailored surface cavities could be somehow compared to randomly distributed ones, even if produced by very different manufacturing techniques.